Conflict Management In Eco-City Development (Spatial References: Lubhu Urban Area In Kathmandu Valley, Nepal And Surabaya City In Indonesia) - Adisukma, Dana; Rana, Shreema; Hayuni, Nurvina; Ulya, Ayu Fitriatul (Fakultas Teknik, Universitas Brawijaya, 2014)
Urban area as one of the busiest space than another spaces that have various applied systems on it. The complexity of social, economic, ecology and culture systems in urban area was needed an effective and efficience management method toward urban sustainable livelihood. Nowadays, the eco-city development in Surabaya City, Indonesia and Lubhu Urban Area, Kathmandu Valley, Nepal has been developed. In addition, it was emerging some problems between the stakeholders. The research aims are identifying and mapping the potential conflict of stakeholder also conceiving new management strategy to reduce its conflict impacts. This research is important because it will define a simulation with stakeholder analysis as its approach through journals and reports. The research method supported by recent condition about those cities. The conclusion of this research shows that all stakeholders have spesific roles between each other. Logically, the more stakeholder involved the more its roles overlaped. Not only Lubhu Urban Area which have the waste water and solid waste problems, but also Surabaya City. The problems caused by socio-politic conflicts and lack of awareness and contribution between private and public sectors. The alternative solution is integrating the interest between public and private sectors with fully support from political stakeholder.Keywords: Development, Eco-city, Potential Conflict, Stakeholders, Surabaya, Lubhu.